Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapos, upper rio Araguaia basin, Brazil - Costa, Wilson J.e.m. (Zootaxa, 2006)
Rivulus kayapo, new species, a member of the Rivulus punctatus species group from the rio Caiapó drainage, upper rio Araguaia basin, is described. It is similar to R. pinima by the absence of bars on the caudal fin and flank in both sexes, in having longitudinal rows of red dots along the entire flanks in both sexes, and in having longitudinally elongated white mark above the caudal spot in females. Rivulus kayapo differs from R. pinima in having more caudal-fin rays, the dorsal-fin origin more posteriorly placed, and fewer scales in the longitudinal and transverse series; and differs from all congeners of the R. punctatus species group by possessing a unique reticulate color pattern on the flanks in males. A key for identification of species of Rivulus from the rio Araguaia-Tocantins basin is provided.